Antioxidant Properties of Cranberry Leaves and Walnut Meal and Their Effect on Nutritional Quality and Oxidative Stability of Broiler Breast Meat - Arabela Elena Untea; Iulia Varzaru; Mihaela Saracila; Tatiana Dumitra Panaite; Alexandra Gabriela Oancea; Petru Alexandru Vlaicu; Iulian Alexandru Grosu (MDPI AG, 2023)
Dietary sources of bioactive compounds in animal diets, are the natural way to produce animal food products with improved nutritional quality. The present study aimed to test the hypothesis of a synergistic effect of bioactive compounds of cranberry leaf powder and walnut meal on the nutritional quality and antioxidant compounds of broiler meat. An experiment was conducted on 160 COBB 500 broiler chickens, housed in an experimental hall with permanent wood shave litter in boxes of 3 m2. The six dietary treatments were based on corn and soybean meal; three experimental groups were fed diets supplemented with cranberry leaves (CLs) with three inclusion rates (0% in the control group and CL 1% and CL 2%); two experimental groups were fed diets supplemented with walnut meal (WM) with two inclusion rates (0% and WM 6%); and two groups were fed diets with a combination of the selected supplements (CL 1% WM 6% and CL 2% WM 6%). The results show that the experimental groups registered higher concentrations of copper and iron compared with the control group. An antagonist effect was noticed on lipophilic compounds, and the lutein and zeaxanthin concentrations presented a dose-dependent increasing effect under CL influence, while vitamin E concentrations decreased in the same manner. The dietary WM positively influenced vitamin E deposits on breast tissue. The dietary supplements did not produce any effect on the primary oxidation products, but the secondary products were influenced, and the maximum effect on the TBARS values were recorded for the dietary combination of CL 1% and WM 6%.